Designing a Website for SMK Satria Jambi - Ardiansyah, Ardiansyah; Hendrawan, Hendrawan; Suratno, Eddy; Syuhada, Rahmad; Haris, Muhammad (Journal of Technology and Computer, 2024)
On the persentation of information which was presented by SMK SATRIA Jambi was still using the conventional method, This information was obtained from particular medias or straight to the scholl. With the result that infomation conveyed effective and efisition. Based on that case a web base information system program was designed. It is expected through this system, the ineffectiveness and the shortcoming in term of information system which exists can be minimized can be easly accessed by people who want to know the information which in SMK SATRIA Jambi as well as the new candidate of new students who will enroll at SMK SATRIA Jambi will make them easier by only filling the given form. The method used in the development of the system is the Waterfall method. While the system modeling tools used by the author is the Use Case Diagrams, Activity Diagrams and Class Diagrams. The programming language used in the design of the SMK Satria Jambi Website is using php and MySQL DBMS. With the programming language that can facilitate the development of the website at SMK Satria Jambi. Being able to facilitate the school in informing profile, achievements, and various other important activities of the school and overcome the old system.